PENGARUH KOORDINASI, KOMPETENSI DAN DISIPLIN TERHADAP KINERJA PEGAWAI UNIT LAYANAN PENGADAAN KEMENTERIAN AGAMA PUSAT (ULP KEMENAG PUSAT) - Donny Feronika Octorano (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract. This study aimed to analyse the effect of coordination, competence and discipline to employee performance ULP MORA Center. Research involving as many as 64 people as a sample of respondents with saturated sampling technique. Data retrieved by using a questionnaire filled with self-rating method. Analysis of data using multiple linear regressionmodels were processed with SPSS. F test showed that coordination, competence, and disciplined work together significant effect on the performance of employees. The results of ttest showed that coordination, competence and discipline influence on employee performance individually. Analysis shows that the correlation between the dimensions of vertical coordination in coordination variables have the strongest correlation with the work on employee performance variable, the variable knowledge competency has the strongestcorrelation with the work on employee performance variables, and corrective discipline to discipline variables correlated The most powerful of the quality of work on employee performance variables. Based on these findings, the employee's performance can be maximized ULP MORA Center through increased vertical coordination (formal meeting), knowledge (training of employees) and corrective discipline (verbal or written warning)Keywords: Coordination, Competence, Discipline, Employee Performance.